Study of a highly boosted Higgs boson decaying to b-jets final states with the ATLAS experiment at CERN - Foti, MG (2021)
The observation of the decay of the Higgs boson to a b ̄b pair in 2018 confirmed the Yukawa interaction and provided the first measurement of a Yukawa coupling to down-type quarks. The most sensitive channel in the H → b ̄b measurement is given by the associated Higgs boson production with a vector boson V decaying leptonically. The main focus is now the measurement of the Higgs boson production cross section as a function of its transverse momentum (pT ). This study is motivated by a wide range of Beyond the Standard Model (BSM) theories predicting an enhancement of V H(H → b ̄b) events at high transverse momentum with respect to the SM expectations. At such high energy regimes, the Higgs boson is highly Lorentz-boosted and the H → b ̄b de- cay is reconstructed in the detector as a single object with a two-prong substructure. This thesis describes the measurement of V H(H → b ̄b) in the boosted regime performed inclusively, as well as in bins of the vector boson trans- verse momentum, for pVT ∈ [250,400[ GeV and pVT ∈ [400,∞[ GeV. The interpretation of these measurements using the Effective Field Theory (EFT) framework is also discussed. The results are based on the full LHC Run 2 dataset collected by the ATLAS experiment, corresponding to an integrated luminosity of 139 fb−1. A very important component of this study is the correct identification of b-jets. A new calibration of the b-jet tagging algorithm at very high transverse momentum, which reduced the uncertainties for high-pT b-jets by 50%, is also included.